Implementasi Pendidikan Inklusi Pada Siswa Hiperaktif Di SD Muhammadiyah Alam Surya Mentari Surakarta Tahun 2016 - Nasrulloh, Ibnu, Minsih, S.Ag, M.Pd (2016)
This reasearch aimed to know the implementation of inclusive education toward hyperactive students in elementary school of Muhammadiyah Alam Surya Mentari Surakarta. The appearance of Inclusive Education for students with special needs promotes the elementary school of Muhammadiyah Alam Surya Mentari Surakarta to take part in supporting that program; it is done to support the children' right to be educated. Among those special needs of inclusive students, one of them is called hyperactive students. Students who move more active than the other students and impulsive. If there is lack of handling, it will bother the process of study for them and for the other students. The worst is that it will create a new problem inside like the difficulty to get socialized and cannot achieve the best in academic. This research used technique analysis data of qualitative research, case study. The data collecting technique of this research are interview, observation and documentation. The implementation of inclusive education in the elementary school of Muhammadiyah Alam Surya Mentari Surakarta had been already good. The utilization of pull out system is the evidence that there is conducted inclusive education in this school. By that system, the students with special needs will be easier to learn the learning materials. Especially for hyperactive students, it is proven by the fact that the impulsive attitude of hyperactive students is getting reduced after given special treatment from the inclusive division of the elementary school of MuhammadiyahAlam Surya Mentari.